Changes in maximal double poling performance during and after moderate altitude training in elite cross-country skiers - Höök, M.; Jensen, K.; Willis, S.; Holmberg, H. C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
In 2014, the Olympic cross-country ski competitions will be held in Sochi, Russia at approximately 1500m altitude. Even moderate altitude can have negative effects on performance in highly trained endurance athletes and individuals may adapt and react differently to altitude exposure. Different skiing techniques (such as double poling) may also be affected by altitude due to the involvement of the upper body. Thus, the purpose of our study was to evaluate changes in double poling performance during and after three weeks of training in moderate altitude in elite skiers.